An effective educational tool for straightforward learning of numerical modeling in engineering electromagnetics. Issue 6 (21st March 2021) - Zhu, Gaojia; Li, Longnv; Xue, Ming; Liu, Tao
Abstract: "Engineering Electromagnetics" is the "most familiar stranger" of college students who major in electrical engineering (EE). Through years of physics learning, the students have had a certain understanding of the basic theories of electromagnetic fields. However, during studying the course, especially the numerical modeling chapter, large‐scale mathematical derivations need to be conducted, which significantly enhance the difficulty for students. The cell method (CM) is a newly established numerical method based on the direct derivation of physical laws in cell‐complexes, and the physical meanings of the equations are clear and definite. By establishing and applying the education platform based on CM, the students' cognition and mastery of electromagnetic theories and numerical techniques can be deepened substantially. In this paper, the electromagnetic field is mathematically modeled based on CM, and the related transformations in the dual cell complexes are illustrated through the Tonti diagram in class. The simulation platform for electromagnetic fields based on CM is established by coding mathematical models. After teaching the methodologies, students are asked to numerically simulate two static field problems with simple geometric structures by using the methodologies, and the results show that they can better understand and perform in numerically related courses based on CM compared with the performances of former students taught with the finite element method. A questionnaire is utilized to survey the teaching effectiveness, and the students' satisfaction is validated by the questionnaire survey. Finally, the methodologies are employed to analyze the electric and magnetic field of two complex engineering cases, and the students can better understand the use of the numerical methods by analysis. Through the numerical simulations based on CM, the students' ability to apply numerical algorithms to solve complex engineering cases is cultivated, and teaching effectiveness of the numerical analysis chapter in Engineering Electromagnetics is enriched.